2017
DOI: 10.1093/ntr/ntx046
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Sustained Decrease in Smoking Urges After Acute Insular Cortex Damage

Abstract: Human lesioning studies that evaluate the insula's involvement in maintaining nicotine addiction make inferences of the insula's role in decreasing urge, but do not use validated instruments that directly assess urges. This study corroborates prior findings using the continuous Questionnaire of Smoking Urges to quantify changes in urge from before lesion onset to immediate and 3-month follow-up time points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The insular cortex contains a high density of hypocretin-1–containing neurons. Immediate and sustained reduction in craving and withdrawal symptoms has been observed in hospitalized smokers following stroke damage to the insular cortex compared to hospitalized smokers without brain lesions ( 46 ).…”
Section: Tobacco Product Use and Nicotine Addictionmentioning
confidence: 99%
“…The insular cortex contains a high density of hypocretin-1–containing neurons. Immediate and sustained reduction in craving and withdrawal symptoms has been observed in hospitalized smokers following stroke damage to the insular cortex compared to hospitalized smokers without brain lesions ( 46 ).…”
Section: Tobacco Product Use and Nicotine Addictionmentioning
confidence: 99%
“…Although, insular damage is associated with increased odds of smoking cessation, those that do relapse tend to remain abstinent for longer periods than those with non-insular damage (Abdolahi et al, 2015a). It has also been shown that smokers with insular damage experience less frequent and severe withdrawal symptoms of nicotine (Abdolahi et al, 2015b) and less smoking urges (Abdolahi et al, 2017). Also, damage to the insula was associated with complete abstinence from all nicotine products (Abdolahi et al, 2015a).…”
Section: Clinical Evidence For the Insulamentioning
confidence: 99%
“…Imaging studies in humans, have heavily implicating the IC in self-referential processes shaping conscious awareness (Kurth, 2010 ; Critchley and Seth, 2012 ; Pais-Vieira et al, 2016 ). Further studies of the local activity and functional connectivity of the IC thus hold particular promise in relation to their link to autism (Odriozola et al, 2016 ), panic disorders (Banzett et al, 2000 ; Brannan et al, 2001 ), anorexia nervosa (Rolls, 1989 , 2005 ; Shelley and Trimble, 2004 ), pain insensitivity (Singh et al, 2006 ; Potvin and Marchand, 2008 ), schizophrenia (Allen et al, 2004 ; Stephane et al, 2010 ), as well as alcohol and nicotine addiction (Fuehrlein et al, 2014 ; Abdolahi et al, 2017 ; Addicott et al, 2017 ).…”
Section: Learning and Re-learning In The Insulamentioning
confidence: 99%